The achievement of pupils taught by master and non-master teachers in selected subjects relationship to teacher characteristics - Abrugena, Teresita Sianquita
District achievement test scores in mathematics, English, Filipino, and Sibika at Kultura of 35 Grades 1 to 6 classes in Laguna showed no significant differences between pupils taught by master teachers and those taught by non-master teachers. The master teachers indicate that their ineffectiveness is due to their non-teaching assignments. Zero-order correlation coefficients identified the following correlates of academic achievement: (1) length of service or experience and (2) among the teachers' personality traits, (a) behavior orientations and tendencies such as compliance with rules/policies, tolerance for games/parties, and involvement of the brightest pupils in school projects; (b) commitment to school and service to pupils even on off-school hours/days, and commitment to pupil welfare; and (c) attitudes toward professional growth and teaching as a noble profession. Enjoyment in teaching and commitment to school are the best predictors of pupil achievement.